Key Approaches to Professional Training of Social Teachers – Experts in Prevention of Teenage Deviant Behavior - Sorochinskaya, Elena; Chaltseva, Irina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article is devoted to the problem of professional training of social teachers in the context of modern society. The authors prove the urgent need to change the content of training programs for social teachers, make alterations into methodological support and mechanisms of academic process organization. The authors share experience of social work aimed at prevention and correction of deviant behavior of children and teenagers of some regions of Russia. The paper covers the main approaches to organization of professional training of social teachers. The authors offer conceptual model of social-teachers preparation that enables to counter the challenges that Russian educational system has to face nowadays.